Shaping Employee Performance: The Mediating Effect of Work Motivation in Situational Leadership - Simbara, Harry; Farida Ferine, Kiki; Isa Indrawan, Muhammad (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2025)
This study examines the impact of situational leadership style on employee performance, with work motivation serving as a mediating variable. The research was conducted at [institution name] with a sample of 60 respondents. A quantitative approach was employed, and data were analyzed using SmartPLS 3. The findings reveal that while situational leadership style does not directly influence employee performance, it positively and significantly affects work motivation. Additionally, work motivation is found to significantly enhance employee performance. The study further indicates that work motivation fully mediates the relationship between situational leadership style and employee performance. These results highlight the critical role of leadership style in fostering employee motivation, which in turn drives performance improvements. Based on these findings, organizations are encouraged to implement adaptive leadership approaches that prioritize boosting employee motivation to achieve optimal performance outcomes.